The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s11011-017-0108-z
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic-like effects of α-asarone in a mouse model of chronic pain

Abstract: α-asarone (ASR) is a major bioactive compound isolated from the rhizome of Acorus tatarinowii Schott and it has extensive biological effects. Clinically, anxiety disorder is a common comorbidity of chronic pain. However, limited information is available regarding the effects of ASR on chronic pain-related anxiety. This study aims to evaluate the anxiolytic effects of ASR in chronic pain mice. Chronic inflammatory pain was induced by hind-paw injection of complete Freund's adjuvant (CFA). Behavioral tests, west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Glutamate and GABA systems were known to generate the opposite forces in neurotransmission and played key roles to the proper function of the CNS. Previous studies showed that α-asarone enhanced GABAergic neurotransmission but decreased glutamatergic release to restore the E/I balance and inhibit the chronic inflammatory pain induced by hind-paw injection of complete Freund’s adjuvant ( Tian et al, 2017 ). The expression level of cytoplasmic polyadenylation element binding protein 1 was reported to correlate to presynaptic E/I release in the regulation of chronic pain ( Yue et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate and GABA systems were known to generate the opposite forces in neurotransmission and played key roles to the proper function of the CNS. Previous studies showed that α-asarone enhanced GABAergic neurotransmission but decreased glutamatergic release to restore the E/I balance and inhibit the chronic inflammatory pain induced by hind-paw injection of complete Freund’s adjuvant ( Tian et al, 2017 ). The expression level of cytoplasmic polyadenylation element binding protein 1 was reported to correlate to presynaptic E/I release in the regulation of chronic pain ( Yue et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…When conducted in an inflammatory pain model, a decrease in time spent in the centre of the OF is observed from one to 28 post‐induction days (Amorim et al, 2014; Chen et al, 2013; Gregoire, Wattiez, Etienne, Marchand, & Ardid, 2014; Guo et al, 2016; Kim et al, 2012; Parent et al, 2012; Sun et al, 2016; Tian et al, 2017; Yue et al, 2018; Table 2). Liu and collaborators tested anxiety‐like behaviours in the acid‐induced hyperalgesia model of fibromyalgia and observed an effect 13 days after induction (Liu et al, 2014; Table 3).…”
Section: Evaluating Anxiety‐like and Depression‐like Behaviours In Anmentioning
confidence: 99%
“…Employed as a traditional Chinese medicine, the rhizome of Acorus tatarinowii Schott has low toxicity and is used to treat dementia, central nervous system‐associated disorders, rheumatosis, and other inflammatory diseases (Xu et al, ; Gao et al, ; Tian et al, ). Previous studies have investigated several extracts from Acorus tatarinowii Schott and found that the lignin‐like components, TO (Xu et al, ) and TN (Zhang et al, ), can both inhibit osteoclastogenesis; however, Tatarinan U (TU) and Tatarinan V (TV) lack this suppressive activity.…”
Section: Introductionmentioning
confidence: 99%